2021
DOI: 10.31234/osf.io/cg38a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proactive or reactive? Neural oscillatory insight into the leader-follower dynamics of early infant-caregiver interaction

Abstract: We know that infants’ ability to coordinate attention with others towards the end of the first year is fundamental to language acquisition and social cognition (Carpenter et al., 1998). Yet, we understand little about the neural and cognitive mechanisms driving infant attention in shared interaction: do infants play a proactive role in creating episodes of joint attention? Recording EEG from 12-month-old infants whilst they engaged in table-top play with their caregiver, we examined the ostensive signals and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Thus, evidence suggests that there is an expectation that our own gaze will be followed, with distinct motivational consequences when this occurs. Awareness that our gaze has been followed takes place very quickly, in less than half a second (Phillips et al, 2022 ), and even this brief time is experienced as compressed, via a “temporal, or intentional, binding effect” (David et al, 2008 ). Relatedly, when another person's gaze-shift occurs rapidly after our own, we sense it as being connected to our own gaze, and this leads to a positive, implicit sense of our agency (Pfeiffer et al, 2012 ; Haggard, 2017 ; Stephenson et al, 2018 ).…”
Section: The Privileged Nature Of Book-sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, evidence suggests that there is an expectation that our own gaze will be followed, with distinct motivational consequences when this occurs. Awareness that our gaze has been followed takes place very quickly, in less than half a second (Phillips et al, 2022 ), and even this brief time is experienced as compressed, via a “temporal, or intentional, binding effect” (David et al, 2008 ). Relatedly, when another person's gaze-shift occurs rapidly after our own, we sense it as being connected to our own gaze, and this leads to a positive, implicit sense of our agency (Pfeiffer et al, 2012 ; Haggard, 2017 ; Stephenson et al, 2018 ).…”
Section: The Privileged Nature Of Book-sharingmentioning
confidence: 99%
“…Such benefits, like those of having one's gaze followed, may, in part, accrue from “action-oriented predictive processing” effects, whereby one's motor intentions elicit predictions about the results of our actions (Clark, 2013 ), with the subsequent, anticipated, events then evoking increased neural responsiveness (Engel et al, 2001 ). These mechanisms, largely studied under experimental conditions, could potentially occur in natural social interactions (de Hamilton, 2021 ; Monroy C. et al, 2021 ), including in book-sharing, such that infant attentional and gestural behaviors entailing anticipation and prediction of parental responses then elicit greater neural activation when those responses occur (Southgate et al, 2009 ; Monroy C. D. et al, 2019 ; Phillips et al, 2022 ).…”
Section: The Privileged Nature Of Book-sharingmentioning
confidence: 99%
“…We also highlight the need to consider bidirectional influences. Whilst co-regulation has often been conceptualised as an adult-driven process, in infancy and in childhood (Bornstein, 2013;Phillips et al, 2021), more recent, dynamic systems perspectives have emphasised that the behavioural patterns of each individual partner can only be understood through consideration of bidirectional process (Fogel, 2017a;Hollenstein, 2015;L. Smith & Gasser, 2005;Yu & Smith, 2017).…”
Section: Methodological Challenge #3mentioning
confidence: 99%
“…Recent research recording neural activity during online social interactions with infants has shown that infant attention is structured through interactive but asymmetric, infant-led processes that operate across the caregiver-child dyad: longer infant attention durations associate with both reactive and dynamic modulation in caregiver behaviours, as well as increases in infants' own endogenous cognitive activity (Phillips et al, under review). During naturalistic triadic interactions, infants are behaviourally and neurally highly responsive to when a caregiver responds contingently to them (Murray & Trevarthen, 1986;Phillips et al, 2021;Tamis-LeMonda et al, 2014). For example, when caregivers respond consistently and contingently to modulations in infant behaviour, this increases the amount and complexity of infants' communicative cues over the duration of an interaction (Goldstein & Schwade, 2008;J.…”
Section: Attention/executive Controlmentioning
confidence: 99%
See 1 more Smart Citation